Glial scarring around intra-cortical MEA implants with flexible and free microwires inserted using biodegradable PLGA needles - Darlot, Fannie; Villard, Paul; Salam, Lara Abdel; Rousseau, Lionel; Piret, Gaëlle (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Many invasive and noninvasive neurotechnologies are being developed to help treat neurological pathologies and disorders. Making a brain implant safe, stable, and efficient in the long run is one of the requirements to conform with neuroethics and overcome limitations for numerous promising neural treatments. A main limitation is low biocompatibility, characterized by the damage implants create in brain tissue and their low adhesion to it. This damage is partly linked to friction over time due to the mechanical mismatch between the soft brain tissue and the more rigid wires. Methods: Here, we performed a short biocompatibility assessment of bio-inspired intra-cortical implants named “Neurosnooper” made of a microelectrode array consisting of a thin, flexible polymer–metal–polymer stack with microwires that mimic axons. Implants were assembled into poly-lactic-glycolic acid (PLGA) biodegradable needles for their intra-cortical implantation. Results and Discussion: The study of glial scars around implants, at 7 days and 2 months post-implantation, revealed a good adhesion between the brain tissue and implant wires and a low glial scar thickness. The lowest corresponds to electrode wires with a section size of 8 μm × 10 μm, compared to implants with the 8 μm × 50 μm electrode wire section size, and a straight shape appears to be better than a zigzag. Therefore, in addition to flexibility, size and shape parameters are important when designing electrode wires for the next generation of clinical intra-cortical implants.